2021
DOI: 10.1002/art.41532
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon–Activated STAT4 Regulation of Follicular Helper T Cell–Dependent Cytokine and Immunoglobulin Production in Lupus

Abstract: Objective. To assess the role of STAT4 activation in driving pathogenic follicular helper T (Tfh) cell secretion of the cytokines interleukin-21 (IL-21) and interferon-γ (IFNγ) in murine and human lupus. Methods. The effect of STAT4-dependent Tfh cell signaling on cytokine production and autoreactive B cell maturation was assessed temporally during the course of lupus in a murine model, with further assessment of Tfh cell gene transcription performed using RNA-Seq technology. STAT4-dependent signaling and cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 51 publications
5
24
0
Order By: Relevance
“…Nevertheless, their conclusion that Tfh cell production of IL-21, IFNγ, and immunoglobulin is dependent on type I IFN-activated STAT4 regulation of Tfh cells may be exaggerated and possibly even misleading. (3). Furthermore, as disease progressed, transcriptional analysis revealed that Tfh cells up-regulated type I IFN-driven gene transcription and acquired an enhanced STAT4 gene signature (3).…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, their conclusion that Tfh cell production of IL-21, IFNγ, and immunoglobulin is dependent on type I IFN-activated STAT4 regulation of Tfh cells may be exaggerated and possibly even misleading. (3). Furthermore, as disease progressed, transcriptional analysis revealed that Tfh cells up-regulated type I IFN-driven gene transcription and acquired an enhanced STAT4 gene signature (3).…”
Section: To the Editormentioning
confidence: 99%
“…We found that although coproduction of IL‐21 and IFNγ is maintained in Tfh cells in lupus despite progressive loss of Bcl6 and T‐bet expression, phosphorylation of STAT4 continued to increase upon type I IFN stimulation (3). Furthermore, as disease progressed, transcriptional analysis revealed that Tfh cells up‐regulated type I IFN–driven gene transcription and acquired an enhanced STAT4 gene signature (3). STAT4 binds and promotes the regulation of IL21 and Ifng during CD4 T cell differentiation (4).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Second, Dong and colleagues found that IFNβ can promote more significant phosphorylation of STAT4 in splenic Tfh cells and Th1 cells at a later stage of disease compared to the predisease stage (8). However, we wonder why the authors did not further investigate the role of IFNβ in regulating IL‐21 and IFNγ production by splenic Tfh cells and Th1 cells by direct stimulation with IFNβ.…”
mentioning
confidence: 99%